Motor Impairment and Developmental Psychotic Risk: Connecting the Dots and Narrowing the Pathophysiological Gap. (11th July 2018) - Poletti, Michele; Gebhardt, Eva; Kvande, Marianne N; Ford, Judith; Raballo, Andrea
Abstract: The motor system in its manifold articulations is receiving increasing clinical and research attention. This is because motor impairments constitute a central, expressive component of the mental state examination and a key transdiagnostic feature indexing disease severity. Furthermore, within the schizophrenia spectrum, the integration of neurophysiological, developmental, and phenomenological perspectives suggests that motor impairment is not simply a generic, extrinsic proxy of an altered neurodevelopment, but might be more intimately related to psychotic risk. Therefore, an increased understanding, conceptualization, and knowledge of such motor system and its anomalies could empower contemporary risk prediction and diagnostic procedures.